Flood Mitigation Strategy in Banjar City, West Java - Faqqih Ma'ruf Anggoro; Agung Adiputra; R. Tricahyono Nur Harsono (Universitas Lambung Mangkurat, 2023)
The flood disaster that occurred in Banjar City was caused by the high intensity of rainfall in each rainy season. The disaster resulted in considerable material and non-material losses. As a result of these impacts, a flood disaster mitigation strategy is needed in Banjar City. Flood disaster mitigation strategies are needed as a form of effort to reduce and manage the risks posed by floods to human health, economic activities, the environment, and cultural heritage. Therefore, this study aims to create a flood disaster mitigation strategy that can be done in Banjar City. This study uses the Analytic Hierarchy Process (AHP) method which aims to obtain weights and determine the priority scale of flood disaster mitigation strategies used. In using this method there are several principles that must be understood in solving problems with AHP, namely decomposition, comparative judgment, synthsesis of priority and logical consistency.The results of the AHP analysis show that regional regulation policy strategies and their implementation (weight 0.195), policy strategies related to coordination between stakeholders (weight 0.185), policy strategies related to disaster risk assessment (weight 0.129), policy strategies related to disaster management funding (weight 0.170), policy strategies related to increasing stakeholder capacity (weight 0.089), strategies for disaster-resilient communities and facilities and infrastructure (weight 0.089), strategies for improving the quality and quantity of human resources (weight 0.085), and strategies for post-disaster recovery (weight 0.059). Based on the results of the AHP analysis, an inconsistensy ratio of 0.014 < 0.1 was obtained, which means that the results of the analysis can be accepted.